The Influence of Sufi Traditions On The Spiritual Life Of The Karakalpaks - Mirjakhan Atamuratova (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
he dissemination of Islam in the Khorezm and Aral Sea region is profoundly intertwined with the teachings of Sufism, which played a pivotal role in shaping the spiritual landscape of the area. Sufi missionaries emerged as the foremost proponents of Islam among the Turkic nomadic peoples, utilising their mystical and inclusive approach to attract a diverse following. This article aims to explore the principal characteristics of Sufism's spread and its subsequent development within the social and spiritual lives of the Karakalpaks. The legacy of Sufism in the Khorezm and Aral Sea region is evident in the ongoing spiritual practices and cultural expressions of the Karakalpaks. Today, elements of Sufi thought continue to influence their rituals, art, and literature, reflecting the enduring impact of Sufism on their social and spiritual life.